Financial Distress Model Among Muslim Millenials : The Moderation Role of Gender - Leo, Gundur; Suherlan, Deiana; Novianti, Ira; Syarief, Mochamad Edman; Suhartanto, Dwi (Entrepreneurship Faculty, Universitas Garut, 2023)
Worries related to financial problems often cause sufferers to experience stress. Stress due to a series of financial problems has increased public awareness of the importance of avoiding personal financial distress. This creates opportunities for unique business development, which can contribute to understanding strategies for strengthening wise management of personal finances. This research aims to provide an understanding of the formation of factors that influence personal financial distress and examine the moderating role of gender. Data was collected through an online questionnaire from 352 Muslim millennials who live in the most populous province in Indonesia, namely West Java. Through the use of PLS ​​for data analysis, this research reveals that religiosity, financial literacy which includes financial knowledge and behavior have a significant effect on personal financial distress. Furthermore, this research shows that gender does not moderate the relationship between religiosity and financial literacy on personal financial distress. These findings provide guidance for financial organizations, governments and educational institutions to jointly improve educational programs that support integrated religious and financial education activities, so that they can contribute to helping society improve their financial management wisely in accordance with sharia principles, and at the same time, contributing to reducing the impact of financial distress.